Harnessing Artificial Intelligence in Foreign Language Education - Fanani, Achmad; Maisarah, Maisarah; Masrur, Mukhamad (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
This study examines the opportunities and challenges of integrating Artificial Intelligence (AI) into foreign language learning through a structured review of relevant literature. The findings show that AI can enhance personalized learning experiences, provide valuable teacher support, and improve access to language resources. However, challenges such as data privacy concerns, algorithmic bias, and the digital divide remain significant obstacles. The study emphasizes the need for ethical AI design, ongoing teacher training, and policies that ensure inclusivity. Additionally, it stresses the importance of continuous evaluation and collaboration among educators, technology developers, and policymakers. This research contributes to a comprehensive understanding of AI’s potential and limitations in transforming foreign language education, while advocating for balanced and responsible implementation.